LEAKAGE OF TRANSAMINASES DURING CRYOPRESERVATION OF CATTLE AND BUFFALO SEMEN IN EGG YOLK TRIS AND SOYA BEAN MILK BASED EXTENDERS - CHAUDHARY, PJ; DHAMI, AJ; CHAUDHARI, DV; PATHAN, MM (The Indian Journal of Animal Reproduction, 2022)
Three healthy and mature bulls each of Gir cattle and Surti buffalo were used to evaluate the comparative efficacy of standard Tris- citric acid-fructose-egg yolk-glycerol (TFYG) extender and soybean based commercially available extenders (Optixcell and Andromed) under split-sample technique for sperm motility and leakage of spermatozoal enzymes transferases (AST-ALT) into the extracellular medium during cryopreservation process. The ejaculates with >70% initial motility were divided into three equal aliquots, and extended @ 100×106 sperm/ml at 34°C with three extenders and frozen using biofreezer following 4h of equilibration. Sperm motility was higher (p<0.05) in Optixcell followed by TFYG and was least in Andromed for both Gir and Surti bull semen. However, AST-ALT activity was similar (p>0.05) between both soyabean based commercial extenders and both had much (2-3 times) lower activities of these enzymes than egg yolk based TFYG extender at all the three stages. In brief, Optixcell gave relatively improved performance during cryopreservation process in both Gir cattle and Surti buffalo semen than the egg yolk based TFYG extender.